Evaluation of the results of intra-articular platelet-rich plasma injections in patients with knee osteoarthritis - Uzun, Öznur (Acta Medica, 2023)
Objective: Osteoarthritis (OA) is the most common form of arthritis, resulting from the degradation of articular cartilage, degradation and proliferative reformation of subchondral bone and a low degree of synovitis that leads to a reduced quality of life. There is no established cure for knee OA. Treatment modalities which have an effect on the underlying biological processes responsible for OA pathogenesis may have potential. One such modality drawing attention is platelet-rich plasma (PRP) injections. In this study, we aimed to evaluate the effects of PRP injections retrospectively in patients with knee OA and the outcomes of two different volume injections. Materials and Method: A total of 314 patients were included in the study. After baseline physical examination, each patient was evaluated with VAS score and WOMAC before the procedure. All the patients received two intra-articular injections one month apart with autologous PRP and were followed up for a minimum period of 1 year (range, 12-34 months). Two weeks after the injections, the physical examinations of the patients and their evaluations with VAS scores and WOMAC criteria were repeated. Results: Both VAS scores and WOMAC scores showed significant differences after the first injection (p<0.05). Although both scores increased after the second injection, the differences were not significant (p>0.05). We also showed that as BMI increased both VAS scores and WOMAC scores increased. Conclusion: Although our study showed that PRP injections have favorable improvements in the management of knee OA such as reducing the pain and decreasing joint stiffness, PRP injections in the treatment of knee OA needs more standardized research.